Etika Uang, Religiusitas, dan Penggelapan Pajak (Studi Kasus Wajib Pajak Orang Pribadi di Kabupaten Gunungkidul) - Faishal Prahatma Ganinda; Kahfi Fikrianoor; Agung Dwi Nugroho; Amir Hidayatulloh (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2020)
This research aims to determine the role of religiosity on the influence of money ethics on tax evasion. The population in this research is individual taxpayers in the Special Region of Yogyakarta. The sample in this research is an individual taxpayer in Gunungkidul district. Sampling in this research uses purposive sampling, with criteria (1) individual taxpayers who have a NPWP, (2) individual taxpayers who carry out business activities or free work. The research data was obtained by distributing questionnaires directly to respondents who met the criteria. This research obtained 42 respondents. Data analysis techniques in this research used Partial Least Square with the help of WarpPLS. This research results show that money ethics influences tax avoidance. However, tax evasion is not influenced by religiosity. This research also proves that the variable of religiosity moderates the influence between money ethics and tax evasion.